White Christmas Pie, ‘smooth as monumental alabaster’: The Past and Future Politics of Shakespearean Cookbooks - Breanne Weber (Journal of Early Modern Studies, 2025)
The article interrogates As You Like It (AYLI), the 1959 cookbook produced by the Seton Guild of Hyattsville, Maryland, as a case study for how the occasional deployment of Shakespearean aesthetics and references across charitable fundraiser cookbooks curates political agendas that ostracize those who do not belong to the communities of (mostly white, upper-class) women who compiled them. Through analysis of the bibliographical elements of the Seton Guild’s AYLI, the article shows how the fragmentary reading methods of the cookbook genre, paired with frequent detached quotation from Shakespeare’s plays – especially those thematically concerned with race – work to detach and distance the white women contributors from the book’s non-American contributors, contributors of color, and the lower-class women their charitable efforts purported to help. It also shows how such cookbooks are important material objects in the history of Shakespearean reception in part because they restore their women compilers to conversations around book history, bibliography, gendered editorial labor, and Shakespearean reception in our work, while simultaneously prompting interrogation of their complicity in the marginalization and erasure of other cultures and communities.